Airport Logistics Post Covid 19 - Kesuma, Hendry Prima (Jurnal Kesehatan & Disiplin Ilmu, 2024)
The purpose of this scientific article research is to prove the results of scientific articles on post-pandemic 19 logistics and look to strengthen the results of researchers, This research methodology uses a qualitative approach and theoretical analysis and analysis of relationships between variables, books and journals, online and offline, obtained from Mendeley, Google Scholar and other online media. The journals reviewed are listed in the Journal Metrics Table below The results of this scientific article researchsay, Airport logistics during the covid 19 pandemic and after the covid 19 pandemic became a field that continued to run in Indonesia, and even when airline companies with restrictions on the covid 19 pandemic, decreased passenger activities, and flight frequency, it was all used by airlines by changing the formation of aircraft carrying passengers to transport cargo, Proving the logistics of this airport with scientific articles that support and researchers strengthen with the results of this scientific article. Recommendations for variables that can be used in the future, namely mobility, energy, environment, customer satisfaction, effectiveness, cost efficiency, performance and service with different research objects and methods.